To determine the new velocity of a satellite when it is moved to an orbital radius of \(6r\), we can use the formula for the orbital velocity:
\[ v = \sqrt{\frac{GM}{r}} \]
where:
- \(G\) is the gravitational constant,
- \(M\) is the mass of the Earth,
- \(r\) is the orbital radius.
If the original orbital radius is \(r\) and the original velocity is \(v\), we can express \(v\) as:
\[ v = \sqrt{\frac{GM}{r}} \]
For the new orbital radius of \(6r\), the new velocity \(v'\) can be expressed as:
\[ v' = \sqrt{\frac{GM}{6r}} \]
We can relate \(v'\) to \(v\):
\[ v' = \sqrt{\frac{GM}{6r}} = \sqrt{\frac{1}{6}} \cdot \sqrt{\frac{GM}{r}} = \sqrt{\frac{1}{6}} v \]
Thus, we can write:
\[ v' = \frac{v}{\sqrt{6}} \]
Among the provided options, this corresponds to:
the fraction with numerator 1 and denominator square root of 6 \(v\).